Influence of management styles on the commitment of local government employees - Đurović Mihajlo Z.; Petrović Dejan Č.; Perić Goran T. (Tehnika, 2023)
Local government as a part of the independent management of local communities represents the basic organization of government. Management is a process of guiding employees toward activities that are relevant to achieving local government goals. Many authors analyzed this subject in their work, while this subject, as well as management styles and the influence of management styles on the commitment of employees in local government, remains unexplored, especially in the context of the Republic of Serbia. The main goal of this research is to look into the influence of management styles on local government employee dedication. This research was conducted during July and August of 2022 and includes a sample of 70 examined local government employees in Serbia. The influence of management styles (transactional, transformational, and passive) on employees was tested with the use of linear regression. The results of this research conclude that transactional leadership has a medium level of influence on local government employee dedication, while the level of transformational management influence on local government employee dedication is high. In the conclusion of this research results are discussed and limitations are set as well as the practical implications of this work.